2022
DOI: 10.1186/s13643-022-02088-y
|View full text |Cite
|
Sign up to set email alerts
|

Can serum autoantibodies be a potential early detection biomarker for breast cancer in women? A diagnostic test accuracy review and meta-analysis

Abstract: Background The increasing incidence of breast cancer necessitates the need to explore alternate screening strategies that circumvent the setbacks of conventional techniques especially among population that report earlier age at diagnosis. Serum autoantibodies is one such potential area of interest. However, their ubiquitous presence across cancer types limits its applicability to any one specific type of cancer. This review was therefore carried out to explore and consolidate available evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Many analyses have shown that practically all tumors leak their constituents into the bloodstream; so, blood may be utilized to examine biomolecules derived from tumors [8]. Researches have concentrated on blood-based biomarkers, such as proteins reviewed previously as well as listed in table 1, which are less intrusive, convenient to determine routinely, and appear to be an option for BC screening [9,10]. -Thioredoxin 1 (Trx1): Trx1 regulates transcription factor DNA binding activity, which is crucial for cancer cell growth [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many analyses have shown that practically all tumors leak their constituents into the bloodstream; so, blood may be utilized to examine biomolecules derived from tumors [8]. Researches have concentrated on blood-based biomarkers, such as proteins reviewed previously as well as listed in table 1, which are less intrusive, convenient to determine routinely, and appear to be an option for BC screening [9,10]. -Thioredoxin 1 (Trx1): Trx1 regulates transcription factor DNA binding activity, which is crucial for cancer cell growth [23].…”
Section: Resultsmentioning
confidence: 99%
“…-ITGA2B (integrin subunit alpha IIb), FLNA (Filamin A), RAP1A (Ras-associated protein-1A), TLN-1 (Talin-1): Previous researches have demonstrated that a individual tumormarker frequently fails to capture sensitivity and specificity in determining a specific malignancy, which can be raised in both normal people and in benign diseases. As a result, a collection of biomarkers was evaluated in order to identify the panel with the greatest accuracy in early identifying BC patients from women without cancer [10]. In Claudia Fredolini et al study, affinity hydrogel nanoparticles coupled with LC-MS/MS analysis was deployed to measure low abundance proteins in serum samples from invasive ductal carcinoma (IDC) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the anti-HSP60 autoantibody has been reported in the serum of cancer patients and can be used as a diagnostic biomarker [ 32 ]. For instance, the presence of this autoantibody has been reported in patients with hepatocellular carcinoma [ 8 , 33 ], breast cancer [ 16 ], ovarian cancer [ 34 ], and colorectal cancer [ 35 ]. In this study, we found 41.8% (38/91) of PCa patients tested positive for the anti-HSP60 autoantibody with a moderate diagnostic performance (AUC = 0.868).…”
Section: Discussionmentioning
confidence: 99%
“…We have also reported significantly higher levels of autoantibodies to p53, ENO1, and BIRC5 in patients with PCa compared to healthy controls [ 13 , 14 ]. In particular, autoantibodies to p53, p16, and p62 were widely detected in multiple tumors [ 15 , 16 , 17 , 18 ]. Additionally, other autoantibodies targeting SOX2, HIF1-α, NY-ESO-1/CTAG1B, MUC1, Her2, GAL1, and GAL3 have been frequently identified in cancer patients [ 16 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation